MIKROENKAPSULASI ASAP CAIR MENGGUNAKAN MALTODEKSTRIN HASIL HIDROLISIS ENZIMATIS DARI PATI UMBI GANYONG, TALAS DAN KENTANG HITAM - , YULIAN ANDRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Liquid smoke has been known to posses several functions such as antioxidant, antibacterial agent, food distinctive flavoring and colorant, as well as natural preservative. However, the material is impractical and difficult to handle during distribution. Microencapsulation has been used to transform pure liquid smoke into microcapsule powder using spray dryer to ease handling. The objectives of the research were to evaluate characteristic of liquid smoke microcapsule prepared using maltodextrin as the result of enzymatic hydrolysis of starch from canna tuber, taro, and black potato, as well as to measure the best wall material and its amount to produce highest quality of liquid smoke microcapsule. Microencapsulation was carried out using spray dryer at inlet temperature of 130ËC and flow rate of 5 ml/minute and 3 kinds of maltodextrin and 1% chitosan, with total soluble solid (TSS) variation of 20, 25 and 30%. Each observed parameters data of phenolic staining analysis using optilab, moisture content, solubility, total phenolic compound, encapsulation efficiency, shape and morphology using Scanning Electron Microscopy (SEM), particle size distribution and volatile profile identification using GC-MS were taken triplicate using completely randomized experiment design. Results of phenol staining showed that the 3maltodextrin combined with 1% chitosan able to trap liquid smoke. Total phenol decrease with the increase of TSS, reversely with microcapsule efficiency. The best result with microcapsule efficiency of 73.51% was obtained using 30% black potato maltodextrin + 1% chitosan SEM observation showed agglomerated spherical microcapsule with smooth surface and average particle size of 0.366Âµm. GC-MS analysis showed that phenolic volatile compound was increased, for microparticle and microcapsule of 18.86% and 23.80%, respectively.